Ribosome Shut-Down by 16S rRNA Fragmentation in Stationary-Phase Escherichia coli. Issue 10 (22nd May 2016) - Luidalepp, Hannes; Berger, Stefan; Joss, Oliver; Tenson, Tanel; Polacek, Norbert
Abstract: Stationary-phase bacterial cells are characterized by vastly reduced metabolic activities yielding a dormant-like phenotype. Several hibernation programs ensure the establishment and maintenance of this resting growth state. Some of the stationary phase-specific modulations affect the ribosome and its translational activity directly. In stationary-phase Escherichia coli, we observed the appearance of a 16S rRNA fragmentation event at the tip of helix 6 within the small ribosomal subunit (30S). Stationary-phase 30S subunits showed markedly reduced activities in protein biosynthesis. On the other hand, the functional performance of stationary-phase large ribosomal subunits (50S) was indistinguishable from particles isolated from exponentially growing cells. Introduction of the 16S rRNA cut in vitro at helix 6 of exponential phase 30S subunits renders them less efficient in protein biosynthesis. This indicates that the helix 6 fragmentation is necessary and sufficient to attenuate translational activities of 30S ribosomal subunits. These results suggest that stationary phase-specific cleavage of 16S rRNA within the 30S subunit is an efficient means to reduce global translation activities under non-proliferating growth conditions. Graphical abstract: